WORKLOAD ANALYSIS AND DETERMINATION OF THE OPTIMAL NUMBER OF WORKERS ON THE OPERATOR'S PART WITH THE WORKLOAD ANALYSIS METHOD APPROACH (Case Study on UHT Department Operators at PT Indolakto Cicurug 3, Processing Ready to Drink Dairy Products) - Danubratha, Nabila Yulia; Sari, Rachi Titi Ramadhani (Universitas Mercu Buana, 2025)
This study aims to analyze the workload of operators in the UHT department of PT Indolakto Cicurug 3 and determine the optimal number of workers using the Workload Analysis (WLA) method approach. The population of this study is all operators in the UHT department of PT Indolakto Cicurug 3 which totals 40 people. The research sample was selected using the purposive sampling method, with one representative from each of the five working parts (Tipper, Mixing, Sterilizer, Filling, and Packing), so that the total sample was five people. The data collection method was carried out through direct observation using the Stopwatch Time Study to measure working time, semi-structured interviews with operators and management to understand work activities and challenges faced, as well as analysis of historical data related to productivity and previous work records. The data obtained was analyzed using the Workload Analysis method, which included the calculation of standard time, allowance percentage, and data uniformity and adequacy tests to ensure the validity of the results. The results showed that there was a workload imbalance in some sections, with some stations experiencing overload (>100%), while others had lower loads (<70%). This imbalance has the potential to affect productivity and labor welfare. Based on the results of the Workload Analysis, this study recommends redistribution of labor to achieve a more optimal balance, which is expected to improve operational efficiency and overall labor welfare.Keywords : Workload Analysis, Workload, Optimal Workforce, UHT Operators, Employee Welfare.